Isoxazoles: synthesis, evaluation and bioinformatic design as acetylcholinesterase inhibitors. (4th November 2013) - Gutiérrez, Margarita; Matus, María Francisca; Poblete, Tomas; Amigo, Jessica; Vallejos, Gabriel; Astudillo, Luis
Abstract Objectives Inhibition of acetylcholinesterase (AChE) is a common treatment for early stages of Alzheimer's disease. In this study, nine isoxazoles derivatives were tested for their in‐vitro AChE activity. The molecular docking showed the interaction of the compounds with the active site. Methods The isoxazoles were synthesized using 1, 3‐dipolar cycloaddition in the presence of sodium hypochlorite. They were also isolated and characterized by spectroscopic methods. The in‐vitro activity was measured by an adapted version of Ellman's assay. Key findings The isoxazoles are described as inhibitors of AChE. The most potent compound in the series exhibited a moderate inhibitory activity (50% inhibitory concentration = 134.87 μm). The design of new compounds was created by using the RACHEL module of the SYBYL software. Conclusions Our research provided enough evidence of the efficacy of isoxazoles as AChE inhibitors. The isoxazoles were synthesized and evaluated as inhibitors of AChE. The docking study based on a novel series of complexes isoxazole with AChE from Electroporus electricus has demonstrated that the ligand bind is similar to the compounds used as reference. To find new candidates with the isoxazole core that act as inhibitors of AChE, part of the structure of the compound 9 was used for de‐novo design. Molecular docking models of the ligand‐AChE complexes suggest that the compound 10 is located on the periphery of the AChE active site.